Two new nor-sesquiterpenoids from Fusarium tricinctum, an endophytic fungus isolated from Ligusticum chuanxiong. Issue 21 (2nd November 2021) - Cao, Yu-Mei; Guo, Da-Le; Jin, Meng-Ying; Tan, Lu; Yang, Tian-Long; Deng, Fang; Gu, Yu-Cheng; Li, Xiao-Hua; Cao, Zhi-Xing; Deng, Yun
Abstract: As part of our search for compounds with cytotoxicity from endophytes of traditional Chinese medicines, two novel nor-sesquiterpenoids (1 –2 ) with a new skeleton containing a tetrahydrofuran moiety were isolated form a rice medium of Fusarium tricinctum, an endophytic fungus isolated from the root of Ligusticum chuanxiong . The structures of these two previously undescribed compounds were elucidated by interpretation of the spectroscopic evidences including NMR correlations as well as MS data. The absolute configurations of these two compounds were confirmed by TD-DFT-ECD calculations. An MTT assay indicated that compound 1 exhibited moderate cytotoxic activity against MV4-11 with an IC50 value of 22.29 μM. Graphical Abstract: